Electrochemical performance of La0.6Sr0.4Co0.2Fe0.8O3-δ cathode material prepared by a sol-gel method assisted with functionalized carbon nanotubes - Nurul Izzati Abd Malek; Ismariza Ismail; Nafisah Osman (Penerbit Universiti Kebangsaan Malaysia, 2020)
A promising perovskite-type oxide ceramics of La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) cathode co-join with BaCe0.56Zr0.34Y0.1O3-δ (BCZY) as supported electrolyte for proton conducting fuel cell (PCFC) was investigated. The ultrafine LSCF was synthesized via a sol-gel process assisted with functionalized carbon nanotubes (f-CNTs) which served as a dispersing agent (denoted as modified-LSCF). The cathode ink of modified-LSCF was prepared by mixing cathode powder with binder that made up of ethyl cellulose and terpeniol. The cathode slurry was then deposited on both surface of the BCZY electrolyte via a spin coating technique to become a symmetrical half-cell. The half-cell of modified-LSCF│BCZY│modified-LSCF was subjected to Electrochemical Impedance Spectroscopy (EIS) and Scanning Electron Microscope/Energy Dispersive X-ray (SEM/EDX). The EIS data revealed the electrochemical reaction of the cell was a thermally activated process that follow the Arrhenius Law. LSCF incorporated with f-CNTs was effectively decreased the ASR value to 0.22 Ωcm2 at 700oC, compared to 0.31 Ωcm2 using pristine-LSCF. The pellet after EIS measurement showed no sign of crack and delamination at cathode/ electrolyte interfaces, with optimum porosity obtained using ImageJ software and its elemental composition still preserved as observed by SEM/EDX analyses. Thus, the LSCF assisted with f-CNTs has a good potential to improve the quality of the cathode for high performance PCFC that operated at intermediate temperature.